Impact of Atrial Fibrillation on Stroke‐Related Healthcare Costs. Issue 6 (25th November 2013) - Sussman, Matthew; Menzin, Joseph; Lin, Iris; Kwong, Winghan J.; Munsell, Michael; Friedman, Mark; Selim, Magdy
Abstract : Background: Limited data exist on the economic implications of stroke among patients with atrial fibrillation (AF). This study assesses the impact of AF on healthcare costs associated with ischemic stroke (IS), hemorrhagic stroke (HS), or transient ischemic attack (TIA). Methods and Results: A retrospective analysis of MarketScan claims data (2005‐2011) for AF patients ≥18 years old with ≥1 inpatient claim for stroke, or ≥1 ED or inpatient claim for TIA as identified by ICD‐9‐CM codes who had ≥12 months continuous enrollment prior to initial stroke. Initial event‐ and stroke‐related costs 12 months post‐index were compared among patients with AF and without AF. Adjusted costs were estimated, controlling for demographics, comorbidities, anticoagulant use, and baseline resource use. Data from 23 807 AF patients and 136 649 patients without AF were analyzed. Unadjusted mean cost of the index event was 20 933 for IS, 59 054 for HS, 8616 for TIA hospitalization, and 3395 for TIA ED visit. After controlling for potential confounders, adjusted mean incremental costs (index plus 12‐month post‐index) for AF patients were higher than those for non‐AF patients by: 4726, 7824, and 1890 for index IS, HS, TIA (identified by hospitalization), respectively, and 1700 for TIA (identified by ED) (all P <0.01). In multivariate regression analysis, AF was associated with a 20% (IS), 13% (HS), and 18% (TIA) increase in total stroke‐related costs. Conclusion: Stroke‐related care for IS, HS, and TIA is costly, especially among individuals with AF. Reducing the risk of AF‐related stroke is important from both clinical and economic standpoints.